Creating wisdom cultures: Integral Coaching as applied foresight in leadership development - Kamppinen, Matti; Jakonen, JP (Approaching Religion, 2015)
Systemic or integral frameworks are needed not only in our projects of creating knowledge and understanding, but also in our attempts to change the world, to make better futures. Transcending the flatland of one-dimensional materiality is pivotal in business, politics and everyday life. Therefore it is understandable that Ken Wilber’s Integral Theory has inspired not only those who wish to cultivate understanding, but also those who have the agenda of creating better futures for human organizations, societies or workplaces. In this article we will first look at the contribution of the futurist Richard Slaughter, who has utilized Wilber’s insights on spirituality in his foresight concepts and practice. Secondly we will focus on leadership development, utilizing Slaughter’s notion of wisdom culture. Thirdly we will present Wilberian integral coaching as a tool for creating wisdom cultures in business. Finally we will discuss how spirituality and wisdom culture are founded on our ontological concepts of human development and reality.